Design of Elliptical Dielectric Resonator Antennas Using Genetic Algorithm and Rayleigh-Ritz Technique - Tadjalli, A.; Sebak, A.; Denidni, T.; Akhlaghi, I. Ahadi- (Applied Computational Electromagnetics Society Journal (ACES), 2022)
In this paper, a specialized genetic algorithm (GA) combined with Rayleigh-Ritz method is used to obtain the dimensions of elliptical dielectric resonators (EDRs) for dual-band, wide-band, or circular polarization (CP) operation. Slot-coupled elliptical dielectric resonator antennas (EDRA’s) and their characteristics are investigated. Parametric studies are presented to study the dependence of the return loss on the slot parameters. These parametric studies are used to optimize the slot dimensions and its position to excite given desired modes.